2015
DOI: 10.1021/cm504545e
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Structure–Property Relationships in Diketopyrrolopyrrole-Based Polymer Semiconductors via Side-Chain Engineering

Abstract: Systematic side-chain engineering has been performed for diketopyrrolopyrrole-selenophene vinylene selenophene (DPP-SVS) polymers to determine the optimal side-chain geometries for the most efficient charge transport, and the structure-property relationship has been thoroughly investigated using a range of analyses. A series of DPP-SVS polymers, ranging from 25-DPP-SVS to 32-DPP-SVS, with branched alkyl groups containing linear spacer groups from C2 to C9 has been synthesized, and the electrical performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
188
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(193 citation statements)
references
References 51 publications
(83 reference statements)
5
188
0
Order By: Relevance
“…[21][22][23][24][25] However, in most of these studies, branched alkyl groups are introduced into the N-position of limited cores, such as isoindigo and diketopyrrolopyrrole. [26][27][28] Here, to further systematically study the branching position effect, we introduced a series of branched alkyl groups with different branching positions (that is, 2-decyltetradecyl (2DT), 3-decylpentadecyl (3DP), 4-decylhexadecyl (4DH), and 5-decylheptadecyl (5DH) groups; Figure 1) into the 3-position of the thiophene ring and the N-position of QA (quinacridone). Then, the 3-alkylthiophenes were combined with the TTD (thienothiophene-2,5-dione) unit, which was copolymerized with the unsubstituted bithiophene unit (PTTD4Ts), and the alkylated QA units were also copolymerized with the unsubstituted bithiophene unit (PQA2Ts; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] However, in most of these studies, branched alkyl groups are introduced into the N-position of limited cores, such as isoindigo and diketopyrrolopyrrole. [26][27][28] Here, to further systematically study the branching position effect, we introduced a series of branched alkyl groups with different branching positions (that is, 2-decyltetradecyl (2DT), 3-decylpentadecyl (3DP), 4-decylhexadecyl (4DH), and 5-decylheptadecyl (5DH) groups; Figure 1) into the 3-position of the thiophene ring and the N-position of QA (quinacridone). Then, the 3-alkylthiophenes were combined with the TTD (thienothiophene-2,5-dione) unit, which was copolymerized with the unsubstituted bithiophene unit (PTTD4Ts), and the alkylated QA units were also copolymerized with the unsubstituted bithiophene unit (PQA2Ts; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…38−41 Kim and co-workers have demonstrated that charge carrier mobility in a vinylene linked thiophene DPP based copolymer can be improved with the substitution of selenophene. 28,42,43 Recently, the nature (p-and n-type) of the charge transport property was finely tuned by attaching a strong electron withdrawing group at the vinylene linkage in a DPP based copolymer. 44,45 Thus, the variety of results obtained for vinylene systems reveals that a clear and conclusive understanding is lacking about the role of the vinylene moiety in organic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al reported a narrow band gap small molecule based on DPP, showing an outstanding PCE of 7.00% [23]. In addition, Kim and coworkers synthesized a series of DPP-selenophene vinylene selenophene polymers with a maximum mobility of 17.8 cm 2 V À1 s À1 by the side chain engineering [24].…”
Section: Introductionmentioning
confidence: 99%